HUBUNGAN KEPEMIMPINAN MANAJER DENGAN KINERJA KARYAWAN PADA HOUSEKEEPING DEPARTEMENT DI DAIMA HOTEL PADANG - ULWAN, NASEH; Elida, Elida; Chair, Ira Meirina (Journal of Home Economics and Tourism, 2014)
The purpose of research is to analyze the relationship between leadership of manager with staff housekeeping performance in Daima Hotel Padang. This study is a descriptive correlational study. The population numbered 30 people of staff housekeeping department, Informant selection techniques in the study using samplingÂ  jenuh technique for 30 people of staff housekeeping department,Data collection techniques with a structured questionnaire based on Likert scale that has been tested for validity and reliability. Based on the survey results revealed the percentage of incoming leadership of manager overall categorized very good (60%), staff housekeeping performance in Daima Hotel Padang overall as good (57%).The results showed that there is a Positive and significant relationship between leadership of manager with staff housekeeping performance in Daima Hotel Padang, It means that the higher the leadership housekeeping manager the performance staff of housekeeping departement also good Keywords: Leadership and Performance